Does Drinking Location Matter? Profiles of Risky Single-Occasion Drinking by Location and Alcohol-Related Harm among Young Men - Bähler, Caroline; Dey, Michelle; Dermota, Petra; Foster, Simon; Gmel, Gerhard; Mohler-Kuo, Meichun (Frontiers in Public Health, 2014)
In adolescents and young adults, acute consequences like injuries account for a substantial proportion of alcohol-related harm, especially in risky single-occasion (RSO) drinkers. The primary aim of the study was to characterize different drinking profiles in RSO drinkers according to drinking locations and their relationship to negative, alcohol-related consequences. The sample consisted of 2746 young men from the Cohort Study on Substance Use Risk Factors (C-SURF) who had reported drinking 6 or more drinks on a single occasion at least monthly over the preceding 12 months. Principal component analysis on the frequency and amount of drinking at 11 different locations was conducted, and two distinguishable components emerged: a non-party-dimension (loading high on theatre/cinema, sport clubs, other clubs/societies, restaurants, and sport events) and a party-dimension (loading high on someone else’s home, pubs/bars, discos/nightclubs, outdoor public places, special events, and home). Differential impacts of drinking location profiles were observed on severe negative alcohol-related consequences (SAC). Relative to those classified as low or intermediate in both dimensions, no significant difference experiencing SAC was found among those who were classified as high in the non-party-dimension only. However, those who were classified as high in the party-dimension alone or in both dimensions were more likely to experience SAC. These differential effects remained after adjusting for alcohol consumption (volume and RSOD), personality traits, and peer-influence (adjusted OR=0.83 [0.68-1.02], 1.57 [1.27-1.96] and 1.72 [1.23-2.41], respectively), indicating independent effects of drinking location on SAC. The inclusion of sociodemographic factors did not alter this association. The fact that this cluster of party-dimension locations seems to predispose young men to experiencing SAC has important implications for alcohol control policies.